Parental education better helps white than black families escape poverty: National survey of children's health - Shervin Assari (Economies, 2018)
According to the Blacks' Diminished Return theory, the health effects of high socioeconomic status (SES) are systemically smaller for Black compared to White families. One hypothesis is that due to the existing structural racism that encompasses residential segregation, low quality of education, low paying jobs, discrimination in the labor market, and extra costs of upward social mobility for minorities, Black families face more challenges for leveraging their education to escape poverty. Aims: Using a nationally representative sample of American families with children, this study investigated racial variation in the effects of highest education of parents on family's ability to scale poverty, defined as the household's income-to-needs ratio. Methods: This cross-sectional study used data from the National Survey of Children's Health (NSCH) 2003-2004-a nationally representative telephone survey that included 86,537 parents of children 0-17 years old. The sample was composed of White (n = 76,403, 88.29%) and Black (n = 10,134, 11.71%) families. The independent variable was highest education of the parents. The dependent variable was household poverty status (income-to-needs ratio). Race was the focal moderator. Linear regression was used in the pooled sample, as well as by race. Results: In the pooled sample, higher education of parents in the household was associated with lower risk of poverty. Race, however, interacted with parental education attainment on household-income-to-needs ratio, indicating smaller effects for Black compared to White families. Lower number of parents and higher number of children in Black families did not explain such racial disparities. Conclusions: The economic gain of parental education on helping family escape poverty is smaller for Black than White families, and this is not as a result of a lower parent-to-child ratio in Black households. Policies should specifically address structural barriers in the lives of all minorities to minimize the diminished return of SES resources across racial minority groups. Policies should also enhance quality of education and reduce the extra cost of upward social mobility for racial minorities. As the likely causes are multilevel, the solutions should also be multilevel. Without such interventions, it may be very difficult if not impossible to eliminate the existing economic and health gap between racial groups.
Keywords: I24; I26; I31; 330; socioeconomic status; income; education; poverty; ethnic groups; blacks; ethnicity; families; parents